2020
DOI: 10.3389/fneur.2020.00248
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease Diagnosis Using Neostriatum Radiomic Features Based on T2-Weighted Magnetic Resonance Imaging

Abstract: Background: Parkinson's disease (PD) is a neurodegenerative disease in which the neostriatum, including the caudate nucleus (CN) and putamen (PU), has an important role in the pathophysiology. However, conventional magnetic resonance imaging (MRI) lacks sufficient specificity to diagnose PD. Therefore, the study's aim was to investigate the feasibility of using a radiomics approach to distinguish PD patients from healthy controls on T2-weighted images of the neostriatum and provide a basis for the clinical dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Second, although the radiomics calculation was automatic, the ROI segmentation was manual, which is prone to interoperator variability and hinders the clinical application of radiomics. Future utility of automatic segmentation might reduce the interoperator variability and improve the clinical feasibility of radiomics ( 31 ). Additionally, we had a heterogeneous data recruited from two institutions with CTA images acquired by four different scanners comprising various protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although the radiomics calculation was automatic, the ROI segmentation was manual, which is prone to interoperator variability and hinders the clinical application of radiomics. Future utility of automatic segmentation might reduce the interoperator variability and improve the clinical feasibility of radiomics ( 31 ). Additionally, we had a heterogeneous data recruited from two institutions with CTA images acquired by four different scanners comprising various protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of radiomics features and convolutional neural networks (CNN) can increase the diagnostic accuracy (Ortiz et al., 2019). Other radiomic analysis focusing on longitudinal SPECT images and T2‐weighted MRI can also enhance the prediction accuracy of PD (Liu et al., 2020; Rahmim et al., 2017). A radiomic study based on PET/CT images extracted high‐order features and trained a SVM model to classify PD and HC subjects, and the results demonstrated that the radiomic method combined with SVM could distinguish PD from HC (Wu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although conventional MRI lacks specificity as a diagnostic aid for PD, 70 a large number of patients show structural microlesions in the basal ganglia, with progressive reductions in whole gray matter, and a volumetric decrease in the caudate, putamen, accumbens, and amygdala. 71,72 In our PD sample, over 80% of patients showed abnormal MRI.…”
Section: Psychometric Phenotypementioning
confidence: 78%